Ectodermal dysplasia-skin fragility syndrome: A rare case report - Subhash Kashyap; Vinay Shanker; Neelam Sharma (Wolters Kluwer Medknow Publications, 2015)
Ectodermal dysplasia/skin fragility syndrome (ED-SFS) is a newly described autosomal recessive disorder characterized by skin fragility and blistering, palmoplantar keratoderma, abnormal hair growth, nail dystrophy, and occasionally defective sweating. It results from mutations in the PKP1 gene encoding plakophilin 1 (PKP1), which is an important component of stratifying epithelial desmosomes and a nuclear component of many cell types. Only 12 cases of this rare genodermatosis have been reported so far. We present an unusual case of ED-SFS in a 12-year boy who was normal at birth but subsequently developed skin fragility, hair and nail deformities, abnormal dentition, palmoplantar keratoderma, and abnormal sweating but no systemic abnormality.